Implications of Issue Salience in the Online News of the 2011 Somali Famine - Dauda, Sharafa; Omar, Bahiyah (2015)
This article explores how major news media and news agencies assigned importance to aspects of the 2011 humanitarian disaster in Somalia. What were the sources that dominated their coverage, and what was the relationship between the sources and the assignment of salience? These issues were investigated through content analyses of online news from Al Jazeera English, Cable News Network International, Pan African News Agency and Reuters. The researchers found different levels of emphasis on news framing functions. The two news agencies, Panapress and Reuters, used similar news framing functions. This suggests that Reuters extended its function of being a news purveyor for news media to a definer of news content for an alternative news agency in a developing nation. Furthermore, the pattern of assigning salience to functions in news framing revealed that because the 2011 famine in Somalia was a humanitarian disaster with catastrophic consequences, the assignment of greater salience to suggestions and to consequences may have been intended to mitigate the disaster itself and prompt urgent action. The distinctions and similarities in assigning functions to news frames may not be unconnected to the functions of ideological structures, editorial policies and in-house style. The study also found a significant relationship between news framing functions and news sources suggesting that news sources played a significant role in assigning salience to the reportage of the humanitarian crisis of the 2011 famine in Somalia.